ESD and Critical Thinking in Science and Social Studies Learning for Grade IV Elementary School - Suryani, Lilis; Nugroho, Ikhlasul Ardi; Wibowo, Setiawan Edi; Haliem, Theresa Dwita (Jurnal Prima Edukasia, 2025)
Education for Sustainable Development (ESD) and critical thinking have been incorporated into elementary school Natural and Social Science (IPAS) learning, although this integration is still limited. This study describes the application of ESD principles and examines the development of critical thinking in grade IV IPAS learning. A case study approach with a qualitative method with six grade IV teachers in Moyudan District, Sleman. Collect data through interviews, classroom observations, and document studies, then analyze using Miles and Huberman’s (1984) framework. The results show that ESD integration is limited to the IPAS subject and has not influenced school programs or culture. Students’ critical thinking competencies developed unevenly, with the analysis of information indicator emerging as the most prominent (43.7%), while the reflection on perspectives indicator showed no development. Limited worksheets further constrained students’ independence, making them reliant on teacher guidance. A whole-school strategy, problem-and project-based learning resources, and institutional support are all necessary, according to these findings. In addition to providing educators with helpful advice, the study demonstrates that Indonesian elementary schools continue to favor analytical skills when implementing ESD.